Business Valuation of the company Le Montmartre - Mičudová, Soňa; Sieber, Patrik, 1977-; Špička, Jindřich, 1981-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2010)
The goal of the diploma thesis is to evaluate company Le Montmartre located in London to know the value of the company when Le Montmartre will be contained from four food shops. It is important to know the value of the company because Le Montmartre business development will take a lot of owner's energy and personal time, so the future value of the business will be a good motivation for him.. This diploma thesis is divided into 2 sections, theoretical and practical. Practical part involved company's introduction, product portfolio, strategic analysis and finance analysis. Company was evaluated by Free cash flow to firm within two phases. Le Montmartre is analysed and evaluated like two separated entities. Le Montmartre is a patisserie and boulangerie and Le Montmartre as a catering company. The value of Le Montmartre as patisserie and boulangerie is estimated on 2 675 295 pounds and Le Montmartre as catering company on 3 739 700 pounds. Company was evaluated on 31.12.2011 in real prices.
Vedoucí práce: Patrik Sieber
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses